Experimental investigation on the dynamic responses of vented hydrogen explosion in a 40-foot container. (25th May 2021) - Hao, Teng-Teng; Wang, Chang-Jian; Yan, Wang-Ji; Ren, Wei-Xin; Yuen, Ka-Veng
Abstract: To investigate the structural dynamics of a container subjected to a vented hydrogen explosion, 48 field tests were conducted in a 40-foot container with roof vents and an end vent. The effects of the hydrogen concentration, ignition position, and obstacles on the evolution of the dynamic responses were investigated. Three stages were generally observed for displacements: (1) At the stage of the vent rupture, the displacement could be approximated as a quasi-static response, and there was a linear relationship between the peaks of positive overpressure and displacement. (2) Structural deformation appeared as reciprocating vibration at the stage of Helmholtz oscillation. (3) The structure exhibited relatively weak irregular fluctuation when high-frequency acoustic oscillation occurred. Two types of the structural acceleration with low and high amplitudes resulting from Helmholtz oscillation and acoustic oscillation, respectively, were clearly observed. For the end-vented explosion, multiple peaks were observed for the displacement at the quasi-static stage due to the rupture, discharge, and external explosion. Moreover, the displacement was sensitive to hydrogen concentration, whereas the number of obstacles and the ignition position had significant influences on the peak acceleration for roof venting. This work conducted the fundamental explanation for the evolution law of structural responses induced by vented hydrogen explosions from the perspective of structural dynamics and enriched the experimental accumulation in a large-scale container with congestion in this field. Graphical abstract: Image 1 Highlights: 48 field tests of the vented hydrogen explosion in a large-scale container were conducted. The effects of concentration, ignition positions and obstacles on the structural dynamics were investigated. Analysis of three stages with vent rupture, Helmholtz oscillation and high-frequency acoustic oscillation were studied. A linear relationship between the peaks of positive overpressure and displacement was found in the stage of the vent rupture. The evolution mechanism of structural dynamics under hydrogen explosion venting was experimentally revealed.